Unveiling Emotional Resonance: A Musical Discourse Analysis of Taylor Swift's 'Midnights Album’ and Its Impact on “Swifties” - Brandon Obenza; Steven Jay A. Silah (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study critically examined Taylor Swift's Midnights album's stylistic devices, thematic elements, and audience reception, employing a qualitative research design. The corpus consisted of the album's thirteen (13) songs, analyzed through the lens of Norman Fairclough's Critical Discourse Analysis (CDA) framework, encompassing description, interpretation, and explanation, and supplemented by I. R. Galperin’s theory of stylistic devices. Additionally, focus group discussions with Swifties provided insights into fan reception. The analysis identified 135 stylistic devices in the album's lyrics, including metaphor (61 instances, 45.19%), imagery (22 cases, 16.30%), simile (13 instances, 9.63%), Hyperbole (8 instances, 5.93%), personification (8 cases, 5.93%), allusion (3 instances, 2.22%), juxtaposition (1 instance, 1%), epistrophe (1 instance, 1%), and rhyme (1 instance, 1%). The recurring thematic elements in the album encompassed self-realization, self-empowerment, escape and solitude, regret and loss, vulnerability, control and manipulation, reclaiming independence, social pressure and expectation, emotional resonance, emotional detachment, emotional turmoil, acceptance, and rejecting conformity. Swifties' reception of the album revealed emergent themes, including self-reflection, self-reliance, emotional acceptance, love, vulnerability, relatability, anxiety, and pain. This study highlights the complex interplay between stylistic expression, thematic depth, and audience engagement in contemporary music discourse, offering insights into the cultural and emotional impact of Taylor Swift's Midnights.